Storm surges versus shore erosion: 21 years (2000–2020) of observations on the Świna Gate Sandbar (southern Baltic coast) - Łabuz, Tomasz Arkadiusz (Quaestiones Geographicae, 2022)
Based on observations spanning 21 years (2000–2020), the article studies the effects of storm surges on the shore of the Świna Gate Sandbar in the southern part of the Pomeranian Bay (southern Baltic Sea). Impacts of selected maximum storm surges in each year were assessed with respect to morphological data collected on the beach and the foredune. The data included parameters of beach-dune erosion as measured along a beach transect before and after each surge. Differences and trends in the shore erosion were related to the sea level (SL), duration of a storm surge [highest storm sea level (HSL) > 1 m], wind-wave sector and wave run-up. The relationships were explored using a sim- ple correlation analysis. The most serious erosion was observed during the heaviest surges [HSL > 1.3 m above the mean sea level (AMSL)], with a wave run-up higher than 3.2 m AMSL. Such surges occurred at about 2-year intervals. The average SL during a surge was 1.2 m AMSL, with a run-up of 2.6 m AMSL. The beach and the lower part of the shore, below that level, were eroded each year. The heaviest surges resulted in an average 5.2 m and 7.0 m dune retreat on the high-beach-accumulative shore and on the low-beach-erosive shore, respectively. The dune was not eroded when the beach height exceeded the wave run-up. The heaviest surges eroded away 12–14 m3 of the beach sand volume. The shore erosion was found to be related to the storm surge duration, the maximum SL, the run-up and the beach height prior to the surge.